PENGARUH PMT BISKUIT UBI JALAR KUNING TEMPE KEDELAI TERHADAP PERUBAHAN BERAT BADAN ANAK WASTING - Imelda Telisa; Podojoyo Podojoyo; Bina Farihani; Yuli Hartati (POLTEKKES KEMENKES MANADO, 2022)
Background: Wasting is weight loss towards height so that child’s body becomes disporpotionate (low weight for height). According to data from the 2017 Basic Health Research (Riskesdas), it shows that in Indonesia the wasting prevalence is 7.8%. cause of the hight prevelance, prevention effort is still needed such as give an additional food for the children. Sweet Potato (Ipomea Batatas L.) is a type of tubers of energy sources for the body, and while soybean tempeh is a source of protein that is easily digestible by the body. Then the food can be used as modification of feeding additional food in children. Methods: Quasi experimental research aims to determine effect of PMT yellow sweet potato and soybean tempeh biscuits on children’s weight change at elementary school number 7 Tanjung Raja. This research conducted for 30 days. Research sample are 70 wasting students. The data was collected using microtoice, digital scales, and recall form 1x24 hours. This data was analyzed using univariat and bivariate analysis. Results: The results refered that the majority of respondents were famale (58%), in age range 7-12 years. From the statistical test result, the avarange of weight treatment group was 23,60 kg to 23,98 kg with p value = 0,00, while the comparison group was 23,73 kg to 23,88 with p value = 0,000. The deviation weigh change in treatment group was 0,38 kg, while the comparison group was 0,14 kg. Conclusion: The conclusion of this research is PMT yellow sweet potato and soybean tempeh biscuits application take an effect into wasting children in elementary school number 7 Tanjung Raja.